Paranormal tourism: study of economics and public policy - Haynes, Everett Drake (Kansas State University, 2016)
Humanity’s belief in the paranormal has shaped cultures, folklore, religion, and influences the arts, customs, politics, and economics. In the modern era, paranormal belief continues to capture public interest, often fueled by popular entertainment and media. With belief in the paranormal on the rise, so are the social and economic implications. Literature and data also shows that paranormal niche tourism is becoming increasingly popular and have an effect on the tourism sector, yet it is poorly understood. The purpose of this study is to ask, “how does paranormal niche tourism affect and relate to local economics and public policy?” New Orleans serves as the subject city due to its rich paranormal history and folklore and thriving tourism economy. I divided data collection into two main phases: 1) surveying paranormal tourists and 2) surveying and interviewing paranormal-related businesses including tour companies, retail and services, and hotels. I distributed online surveys to paranormal tourists to collect data pertaining to demographics, education, employment, belief, belief influencers, travel habits, and costs. In addition, I conducted online surveys and personal interviews with businesses relating to paranormal tourism in regards to business model, marketing, revenue, employment, local community impact, and public policy impacts. A site visit provided further insight and immersion into paranormal tourism itself. Results indicate that paranormal tourism is positively impacting local communities and that public policy in New Orleans has both positively and negatively affected tourism. The results from this research provide insight in how other communities can accommodate paranormal tourism through policy and how businesses can also capitalize on this growing trend.
Keywords: Paranormal tourism; Paranormal economics; Planning; Paranormal tourist; Ghost tourism; Niche tourism